The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3390/v7072788
|View full text |Cite
|
Sign up to set email alerts
|

Ultra Deep Sequencing of a Baculovirus Population Reveals Widespread Genomic Variations

Abstract: Viruses rely on widespread genetic variation and large population size for adaptation. Large DNA virus populations are thought to harbor little variation though natural populations may be polymorphic. To measure the genetic variation present in a dsDNA virus population, we deep sequenced a natural strain of the baculovirus Autographa californica multiple nucleopolyhedrovirus. With 124,221X average genome coverage of our 133,926 bp long consensus, we could detect low frequency mutations (0.025%). K-means cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
83
4
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(93 citation statements)
references
References 67 publications
4
83
4
2
Order By: Relevance
“…We previously described our generation 0 virus population (Chateigner et al 2015), obtained by in vivo amplification of an archival sample. AcMNPV-WP10 was extracted from a one-cycle infection of a large number of highly susceptible hosts (Trichoplusia ni), minimizing the selection pressure on viral genomes.…”
Section: Virus and Bioassaysmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously described our generation 0 virus population (Chateigner et al 2015), obtained by in vivo amplification of an archival sample. AcMNPV-WP10 was extracted from a one-cycle infection of a large number of highly susceptible hosts (Trichoplusia ni), minimizing the selection pressure on viral genomes.…”
Section: Virus and Bioassaysmentioning
confidence: 99%
“…For baculoviruses, which infect pest caterpillars, transmission mainly occurs via direct ingestion of viral particles, on the form of occlusion bodies (OBs), which are released after the death and liquefaction of the previous host (Slack and Arif 2006). An individual baculovirus particle, such as the natural isolate of Autographa californica multiple nucleopolyhedrovirus (AcMNPV) carries many genetically diverse genomes, harboring different single nucleotide variations (SNVs), insertions or deletions (INDELs) (Chateigner et al 2015;Gilbert et al 2014Gilbert et al , 2016. It is thus a population of individual virus genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Shotgun sequencing and partial genome assembly is biased towards identification of dominant genotypes or taxa as a result of the limited read depth across multiple whole genomes [10,12,13]. Amplicon sequencing introduces bias resulting from gene copy number, selection of primers, and classification based on limited span of the genome [2,7,12,14].…”
Section: Introductionmentioning
confidence: 99%
“…Shotgun data can also be used to infer an approximate total number of strains within an isolate and the relative abundance of taxonomic clusters of strains within this population [13,19], but cannot determine the relative abundance of individual strains or abundance of strains that may contain multiple polymorphisms distributed across fragmented reads.…”
Section: Introductionmentioning
confidence: 99%
“…Baculovirus species have been described using restriction endonuclease digestion profile and Sanger sequencing, and more recently by Next Generation Sequencing (NGS) [10,11,16,17,23,26,27,28,29]. Previous research has shown that HaSNPV and HzSNPV share sequence similarity of up to 99.9%, but could be distinguished by a small number of nucleotide substitutions and by open reading frame (ORF) insertions and deletions in the published consensus genome [17,30,31].…”
Section: Introductionmentioning
confidence: 99%